Beyond supervised therapy: Promoting behavioral changes in people with MS. (September 2019) - Plow, Matthew; Finlayson, Marcia
A critical aspect of many rehabilitation interventions for people with multiple sclerosis (MS) is incorporating strategies that support behavior change. The main purpose of this topical review was to summarize recent randomized clinical trials (RCTs) of rehabilitation interventions in which participants learn and apply skills or engage in healthy behaviors. The Capability, Opportunity, Motivation, and Behavior (COM-B) framework was used to broadly classify behavior-change strategies. The included RCTs varied widely in terms of dosing, delivery format, and types of interventionist. Commonly used behavior-change strategies include education, persuasion, and training. We recommend that researchers and clinicians use frameworks like Behavior Change Wheel and Behavior Change Technique Taxonomy to describe and classify intervention strategies used to promote behavior change. We also recommend more sophisticated RCTs be conducted (e.g. sequential multiple assignment randomized trial and three-arm RCTs) to better understand ways of promoting behavior change in rehabilitation interventions.